PERAN INOVASI PRODUK MEMEDIASI ORIENTASI PASAR TERHADAP KINERJA PEMASARAN - Putra, I Gede Dharmana; Rahanatha, Gede Bayu (E-Jurnal Manajemen, 2017)
This study aims to explain the effect of market orientation on product innovation and marketing performance, the effect of product innovation on marketing performance, and the role of product innovation in mediating the influence of market orientation on marketing performance. This research was conducted on the owner or manager of UMKM silver handicrafts in Celuk Village, Gianyar Regency. The method used to determine the sample is non-probability in the form of purposive sampling with sample size of 71 respondents. The data was collected by spreading the questionnaire directly in Celuk Village. Data analysis technique used is path analysis and test of sobel. The results showed that market orientation has a positive and significant effect on product innovation. Market orientation has a positive and significant impact on marketing performance. Product innovation has a positive and significant effect on marketing performance. Product innovation significantly mediates the effect of market orientation on marketing performance.